Role and Effectiveness of IOT in E-Learning: A Digital Approach for Higher Education - Muhammad Ayoub Kamal; Ali, Attra; Laiq Muhammad khan (Innovative Computing Review, 2023)
Internet of things (IOT) is an emerging technology, which has facilitated the abiding connection of real and virtual objects. Its developmental influence has caused a predictable impact on higher education, especially E-learning. Previous studies indicated that the prime aim of IOT is to transform traditional education into a flexible and effective learning approach by creating a digital or virtual learning environment. Consequently, the current study aims to evaluate the effective role of e-learning in higher educational institutions by investigating faculty’s overall interactions with this new learning platform. A comprehensive questionnaire was used for data collection from faculty members of several local universities to assess how instructors see E-learning. The analysis and presentation of the data have all employed tables, graphs, and other pertinent visual representations of the data. Data analysis of teachers’ response displayed that viability, abundant material, affordability, mobility, and enhanced concentration are keys features of e-learning that attract teachers. Thus, teachers believe/see e-learning as an adaptable dynamic change to meet educational needs in challenging times. Additionally, teachers also highlighted certain issues that they face while adapting e-learning such as inadequate internet connectivity, limited access, insufficient internet speed in remote areas, online real-world subjects are harder to understand, and cyber security problems. These problems need to be addressed at large to improve the efficiency and potential of e-learning in Pakistan.